Lachesis stenophrys venom reduces the equine antibody response towards Bothrops asper venom used as co-immunogen in the production of polyspecific snake antivenom. (1st September 2015) - Arroyo, Cynthia; Solano, Sergio; Herrera, María; Segura, Álvaro; Estrada, Ricardo; Vargas, Mariángela; Villalta, Mauren; Gutiérrez, José María; León, Guillermo
Abstract: The anti-bothropic activity of an antivenom prepared from the plasma of horses immunized with Bothrops asper venom (anti-B antivenom) was compared with a similar formulation produced from the plasma of horses immunized with a mixture of B . asper and Lachesis stenophrys venoms (anti-BL antivenom). Likewise, a comparison between the anti-lachesic activity of the anti-BL antivenom and a similar formulation prepared from horses immunized only with L . stenophrys venom (anti-L antivenom) was performed. The anti-BL antivenom had lower concentration of anti-bothropic antibodies than the anti-B antivenom. This difference was associated to a lower response towards all components of B . asper venom, but particularly towards some D49-phospholipases A2 (PLA2 s) and PIII-metalloproteinases. Consequently, the anti-BL antivenom was less effective neutralizing lethal, coagulant, defibrinogenating, PLA2, and myotoxic activities of B . asper venom. On the other hand, anti-BL and anti-L antivenoms showed similar concentration of anti-lachesic antibodies, and similar capacity to recognize the HPLC fractions of L . stenophrys venom and to neutralize lethal, coagulant, proteolytic, hemorrhagic, PLA2 and myotoxic activities induced by this venom. It is concluded that, when used as co-immunogens, the venom of L . stenophrys reduces the antibody response towards B . asper venom, whereas the latter does not affect the anti-lachesic response. Highlights: Some snake venoms have immunomodulatory properties. Venoms of B . asper and L . stenophrys are used to produce antivenoms in horses. The lachesic venom reduces the antibody response towards the bothropic venom. The bothropic venom did not affect the response towards the lachesic venom.